2009
DOI: 10.1111/j.1538-4616.2009.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Solicitations Matter in Bank Credit Ratings? Results from a Study of 72 Countries

Abstract: Would the credit ratings of unsolicited banks be higher if they were solicited? Alternatively, would the credit ratings of solicited banks would be lower if they were unsolicited? To answer these questions, we use an endogenous regime-switching model and data from 460 commercial banks in 72 countries, excluding the United States, for the period 1998-2003. The answer to both questions is yes. Our results show that the observed differences between solicited and unsolicited ratings can be explained by both the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 19 publications
2
34
0
2
Order By: Relevance
“…Our results provide tentative, but not conclusive, evidence that the downward bias is, indeed, more pronounced when bank opaqueness is high. Both results are novel and nicely complement the results by Poon et al (2009). Finally, in contrast to most of the earlier studies, our dataset is very clear and uncontaminated because we employ S&P rating data for non-U.S. firms, where the rating status is directly observable and verifiable.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our results provide tentative, but not conclusive, evidence that the downward bias is, indeed, more pronounced when bank opaqueness is high. Both results are novel and nicely complement the results by Poon et al (2009). Finally, in contrast to most of the earlier studies, our dataset is very clear and uncontaminated because we employ S&P rating data for non-U.S. firms, where the rating status is directly observable and verifiable.…”
Section: Introductionsupporting
confidence: 64%
“…ratings are downward biased for Asian and international banks, respectively. Most recently, using an endogenous regime-switching model for a sample of non-U.S. banks with S&P ratings between 1998 and 2003, Poon et al (2009) show that unsolicited bank ratings would be higher if they were solicited and, vice versa, that solicited bank ratings would be lower if they were unsolicited. By decomposing the observed rating level differences into two components -the clientele effect, caused by a bank's financial profile, and the treatment effect, due to the solicitation status -they address a potential self-selection bias, but conclude that, at times, the solicitation-status effect may outweigh it.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, relative size helps determine market position, extent of diversification, and financial flexibility (S&P 2008). Poon and Firth (2005) and Poon, Lee, and Gup (2009) found that larger banks have more incentive to seek credit ratings and that they tend to have higher bank ratings. Because rating agencies consider sovereign credit risk to be important in assessing the credit standing of banks and corporations (S&P 1997, 1998b), S&P's sovereign credit rating (SOV) is included in the rating determinant models to explain LTRs.…”
Section: Sample and Datamentioning
confidence: 99%
“…These growing concerns and controversies might have been triggered by the observation that unsolicited credit ratings, on average, tend to be lower than the solicited ratings (see, for example, Poon 2003;Gan 2004;Shimoda and Kawai 2007;Fairchild, Flaherty, and Shin 2009;and Poon, Lee, and Gup 2009). Some researchers asked whether unsolicited ratings were lower than they deserved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation